2005
DOI: 10.1097/01.aia.0000166335.69251.06
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes After Paravertebral Blocks

Abstract: Paravertebral block (PVB) was introduced by Hugo Sellheim almost a century ago for use in abdominal surgery in early 1919. 1 Eason and Wyatt 2 revived this technique in 1979. Although investigators used it extensively in Europe in patients admitted to the hospital, Wood et al 3 introduced it in the ambulatory setting for the first time in 1981. It is only since the report of Weltz et al 4 in 1995 on the management of breast cancer surgery as an ambulatory surgical procedure that the use of this technique was w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…The reported advantages of TPVB include a simplicity of technique, safety of performing in sedated and ventilated patients, lower amount of local anesthetic loss in intercostal drains as compared to intrapleural block, a low incidence of complications, facilitation of early mobilization, and early discharge. [ 2 11 ] The feasibility, efficacy, and safety of landmark-guided TPVB in on pump cardiac surgery was first studied by Canto et al . in 111 patients (47 after induction of anesthesia and 64 in awake sitting position).…”
Section: Discussionmentioning
confidence: 99%
“…The reported advantages of TPVB include a simplicity of technique, safety of performing in sedated and ventilated patients, lower amount of local anesthetic loss in intercostal drains as compared to intrapleural block, a low incidence of complications, facilitation of early mobilization, and early discharge. [ 2 11 ] The feasibility, efficacy, and safety of landmark-guided TPVB in on pump cardiac surgery was first studied by Canto et al . in 111 patients (47 after induction of anesthesia and 64 in awake sitting position).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, inadequately‐treated postoperative pain compromises respiratory function and may result in adverse effects in children undergoing aortic coarctation repair. Numerous studies have demonstrated that, in adult patients, after thoracotomy, the most favorable outcomes were obtained when adequate analgesia was provided by paravertebral block . It is reported that paravertebral block procedure is technically easy to learn and as effective as epidural block .…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have demonstrated that, in adult patients, after thoracotomy, the most favorable outcomes were obtained when adequate analgesia was provided by paravertebral block . It is reported that paravertebral block procedure is technically easy to learn and as effective as epidural block . It also improves patient's well‐being in terms of reduction in opioid use, postoperative nausea and vomiting, less urinary retention, improved hemodynamic changes, early discharge, prevention of pulmonary functions, and improvement in oxygenation and reduction in stress response .…”
Section: Discussionmentioning
confidence: 99%
“…Paravertebral block is equianalgesic to a thoracic epidural for thoracotomy, according to Davies et al [13], with fewer complications such as urinary retention, PONV, or hypotension. Ganapathy et al [14] examined outcomes after PVBs and determined that, in breast surgery, PVBs resulted in decreased opioid use in the recovery room, lower frequency of PONV, and faster recovery from anesthesia. In patients who underwent thoracic surgery, pulmonary function was better preserved, there was a shorter hospital stay, and patient care costs were reduced when PVBs were used.…”
Section: Discussionmentioning
confidence: 99%